High-performance supercapacitors based on hierarchically porous carbons with a three-dimensional conductive network structure. Issue 16 (29th March 2019) - Zou, Jizhao; Tu, Wenxuan; Zeng, Shao-Zhong; Yao, Yuechao; Zhang, Qi; Wu, Hongliang; Lan, Tongbin; Liu, Shiyu; Zeng, Xierong
Abstract : Novel clews of carbon nanobelts (CsCNBs), which have high specific surface area, three-dimensional conductive network structure, hierarchically porous framework and excellent hydrophilicity, have been successfully prepared by carbonization and KOH activation. Abstract : Clews of polymer nanobelts (CsPNBs) have the advantages of inexpensive raw materials, simple synthesis and large output. Novel clews of carbon nanobelts (CsCNBs) have been successfully prepared by carbonizing CsPNBs and by KOH activation subsequently. From the optimized process, CsCNBs*4, with a specific surface area of 2291 m 2 g −1 and a pore volume of up to 1.29 cm 3 g −1, has been obtained. Fundamentally, the CsCNBs possess a three-dimensional conductive network structure, a hierarchically porous framework, and excellent hydrophilicity, which enable fast ion diffusion through channels and a large enough ion adsorption/desorption surface to improve electrochemical performance of supercapacitors. The product exhibits a high specific capacitance of 327.5 F g −1 at a current density of 0.5 A g −1 in a three-electrode system. The results also reveal a high-rate capacitance (72.2% capacitance retention at 500 mV s −1 ) and stable cycling lifetime (95% of initial capacitance after 15 000 cycles). Moreover, CsCNBs*4 provides a high energy density of 29.8 W h kg −1 at a power density of 345.4 W kg −1 in 1 M tetraethylammonium tetrafluoroborate/acetonitrile (TEABF4 /AN) electrolyte. These inspiring results imply that this carbon material with a three-dimensional conductive network structure possesses excellent potential for energy storage.